“Dancing Eye Syndrome” Secondary to Opsoclonus-Myoclonus Syndrome in Small-Cell Lung Cancer - S. Laroumagne; Xavier Elharrar; B. Coiffard; J. Plojoux; H. Dutau; D. Breen; P. Astoul (Case Reports in Medicine)
Among paraneoplastic neurologic disorders (PND), opsoclonus-myoclonus syndrome, so-called “dancing eye syndrome,” is a rare disorder combining multivectorial eye movements, involuntary multifocal myoclonus, and cerebellar ataxia. Although several paraneoplastic antibodies against postsynaptic or cell-surface antigens have been reported, usually most patients are serum antibody negative. We report a 65-year-old patient with opsoclonus-myoclonus syndrome revealing a small-cell lung carcinoma. If serologic antineuronal anti-body screening was negative, autoantibodies against glutamic acid decarboxylase (anti-GAD) were positive. Despite the specific anticancer treatment and high dose corticosteroids, the patient developed a severe and progressive encephalopathy and died 10 days later.